Dynamic equilibrium of cellular plasticity: The origin of diseases - Kwan, Edmund K.; Flowers, Jonathan; Ming, Xue (Frontiers in Ecology and Evolution, 2023)
Since its inception, cellular plasticity has undergone many iterations. Today we define it as the ability of mature, terminally differentiated cells to change their identity, meaning lineage change of the cells by transdifferentiation, dedifferentiation and reprogramming. This process does not involve a single DNA sequence change or a mutation. We now know that the behavior of a cell is profoundly affected by the surrounding environment. There is a perpetual pressure placed on the genetic expression of the cells. The external environment and specifically the microenvironment of the cells greatly influences the genotype. There is a never-ending dynamic interplay between the genotype and the phenotype. Incremental phenotypic adjustments are continuously occurring to yield improved cell survival. These changes are beneficial to the cells at a given moment. As the environmental condition declines, then more extensive phenotypic transformation (via transdifferentiation and dedifferentiation) can follow. When the cellular environment further deteriorates, cellular plasticity can trigger a pathologic sequence that eventually leads to cancers/diseases. These modifications are all part of an adaptive process that enhances the survival of the cells. They can offer short term advantages, but they can also lead to diseases. Oxygen level plays a pivotal role in the development of chronic diseases. Cellular response to hypoxia is mediated through hypoxia inducible factor (HIF). HIF is an oxygen sensor that is closely involved in the pathophysiologic adaptation to hypoxia. Our hypothesis centers on hypoxia as the major stressor initiating cellular plasticity and restoring normoxia is an essential step in the healing process. This theory could be tested using chronic pathological processes in animal models whereby achieving an adequate cellular oxygen level could improve or halt both plastic change and diseases.